The State of food and agriculture, 2005 : agricultural trade and poverty : can trade work for the poor? (Rome Food and Agriculture Organization of the United Nations, 2005)
Can trade work for the poor? Trade and trade liberalization affect the poor and food-insecure. Trade can be a catalyst for change, promoting conditions that enable the poor to raise their incomes and live longer, healthier and more productive lives. B ut because the poor often survive on a narrow margin, they are particularly vulnerable in any reform process, especially in the short run as productive sectors and labor markets adjust. Opening national agricultural markets to international competition - especially from subsidized competitors - before basic market institutions and infrastructure are in place can undermine the agriculture sector with long-term negative consequences for poverty and food security. Among the many important lessons from this analysis is the need for policy-makers to consider carefully how trade and complementary policies can be used to promote pro-poor growth. The report recommends a twin-track approach: investing in human capital, institutions and infrastructure to enable the poor to take advantage of trade-related opportunities, while establishing safety nets to protect vulnerable members of society.
"TC/P/A0050E/1/11.05/3900"--P. [4] of cover.
Included in the back pocket is a mini CD-ROM of the "FAO Statistical Yearbook 2004 Vol. 1/1" in Arabic, Chinese, English, French and Spanish.
Subtitle from cover.
Includes bibliographical references.
Keywords: Agriculture -- Developing countries; Food supply -- Developing countries; Free trade -- Developing countries; Poor -- Developing countries